62.4k views
4 votes
3x²+7x+2

pls explain <3 tyy

User Lonegunman
by
5.2k points

1 Answer

1 vote

(x + 2)(3x + 1)

When the coefficient of the x² term is not 1 , then for a quadratic in standard form

That is ax² + bx + c (a ≠ 0) then to factor we consider the factors of the product ac which sum to give b

for 3x² + 7x + 2

the factors of the product 3 × 2 = 6 which sum to + 7 are + 6 and + 1

split the middle term using these factors

= 3x² + 6x + x + 2 → (factor by grouping )

= 3x(x + 2) + 1(x + 2) → (take out the common factor (x + 2))

= (x + 2)(3x + 1)

3x² + 7x + 2 =(x + 2)(3x + 1) ' in factored form '


User Keyur Padalia
by
5.1k points